Response to Mughal et al, re: “The Biomedical Publications Industry Must Change to Better Serve the Needs of Science and Scientists” - Michael M. Lederman; Neil Greenspan (Pathogens and Immunity)
We thank Abeera Saleem Mughal and Hafiz Shahbaz Zahoor for their letter regarding our recent editorial “The Biomedical Publications Industry Must Change to Better Serve the Needs of Science and Scientists” [1].